The pH and pCO2 dependence of sulfate reduction in shallow-sea hydrothermal CO2 – venting sediments (Milos Island, Greece) - Bayraktarov, Elisa; Price, Roy E.; Ferdelman, Timothy G.; Finster, Kai (Frontiers in Microbiology, 2013)
Microbial sulfate reduction is a dominant process of organic matter mineralization in sulfate-rich anoxic environments at neutral pH. Recent studies have demonstrated sulfate reduction in low pH environments, but investigations on the microbial activity at variable pH and CO2 partial pressure are still lacking. In this study, the effect of pH and pCO2 on microbial activity was investigated by incubation experiments with radioactive 35S targeting sulfate reduction in sediments from the shallow-sea hydrothermal vent system of Milos, Greece, where pH is naturally decreased by CO2 release. Sediments differed in their physicochemical characteristics with distance from the main site of fluid discharge. Adjacent to the vent site (T ~ 40 – 75 °C, pH ~ 5), maximal sulfate reduction rates were observed between pH 5 – 6. Sulfate reduction in hydrothermally influenced sediments decreased at neutral pH. Sediments unaffected by hydrothermal venting (T ~ 26°, pH ~ 8) expressed the highest sulfate reduction rates between pH 6 – 7. Further experiments investigating the effect of pCO2 on sulfate reduction revealed a steep decrease in activity when the partial pressure increased from 2 to 3 bar. Findings suggest that sulfate reducing microbial communities associated with hydrothermal vent system are adapted to low pH and high CO2, while communities at control sites required a higher pH for optimal activity.